The degree of using modern economics in education from the point of view of faculty members in Jordanian universities - Al- Hawamdeh, Hiam Alyan (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the degree of use of modern economics in education from the viewpoint of faculty members in Jordanian universities. 92) of the faculty members in Jordanian universities and using the statistical program (SPSS) where the statistical program (SPSS) was used. The results of the study showed that the degree of using modern economics in education from the viewpoint of faculty members in Jordanian universities obtained a total average (4.22) That is, to a (significant) degree, and it was found that there were no statistically significant differences at the level (α ≤ 0.05) between the average responses of the study sample members towards the degree of using modern economics in education in Jordanian universities, and based on the results of the study, The researcher recommended recommendations, the most important of which is to spread awareness among those who are going to choose their majors in universities to choose the disciplines required in the labor market to ensure that they get jobs upon their graduation, and to encourage professions and industry because of their importance and the society’s need for them like other scientific disciplines.